Partial Quark-Lepton Universality and Neutrino CP Violation. (1st October 2015) - Liao, Jiajun; Marfatia, D.; Whisnant, K.
Abstract : We study a model with partial quark-lepton universality that can naturally arise in grand unified theories. We find that constraints on the model can be reduced to a single condition on the Dirac CP phaseδ in the neutrino sector. Using our current knowledge of the CKM and PMNS mixing matrices, we predict- 32 . 4 ° ≤ δ ≤ 32 . 0 ° at2 σ .